2018
DOI: 10.1080/09540261.2018.1514295
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of sex-based differences in opioid-based effects

Abstract: Background: There are several biological factors that might play a role in physiological response to opioids and/or the onset of problematic opioid use; however, sex-based differences in non-analgesic opioid-based effects are poorly understood. The goal of this review is to provide a current analysis of the preclinical literature on sex-based differences in response to endogenous and exogenous opioids, including the interplay between sex hormones and opioid receptor-mediated neuronal activity and associated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…These data 487 suggest that for females, body temperature may be an important withdrawal sign during both the 488 acute and protracted withdrawal period, though males may only show a signal on body 489 temperature during the protracted period. These findings converge with other preclinical evidence 490 that sex mediates some opioid effects (Huhn, Berry, & Dunn, 2018). Current human clinical data 491 on this topic are limited to differences in treatment presentation between men and women (Huhn,492 Berry, & Dunn, 2019), neonatal abstinence syndrome following prenatal opioid exposure (Klaman 493 et al, 2017), and menstrual cycle abnormalities and amenorrhea following chronic opioid 494 exposure (Santen et al, 1975;Schmittner et al, 2005).…”
Section: Sex-specific Effectssupporting
confidence: 58%
“…These data 487 suggest that for females, body temperature may be an important withdrawal sign during both the 488 acute and protracted withdrawal period, though males may only show a signal on body 489 temperature during the protracted period. These findings converge with other preclinical evidence 490 that sex mediates some opioid effects (Huhn, Berry, & Dunn, 2018). Current human clinical data 491 on this topic are limited to differences in treatment presentation between men and women (Huhn,492 Berry, & Dunn, 2019), neonatal abstinence syndrome following prenatal opioid exposure (Klaman 493 et al, 2017), and menstrual cycle abnormalities and amenorrhea following chronic opioid 494 exposure (Santen et al, 1975;Schmittner et al, 2005).…”
Section: Sex-specific Effectssupporting
confidence: 58%
“…Thus, this paper should be conceptualized as a narrative summary to stimulate future investigations. Finally, despite evidence that many opioid effects may be mediated by gonadal hormones (Huhn et al, 2018) the majority of preclinical and human studies reviewed herein evaluated predominately (and often exclusively) male samples. More research is needed to determine whether medications are equally effective for both sexes, particularly in light of data suggesting hormones impact craving and relapse vulnerability for other drugs of abuse (e.g., Carpenter et al, 2006;Franklin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…1; Table 1) that vary across individuals with regard to incidence and severity; no demographic or drug use characteristics have been identified that reliably predict the severity of human opioid withdrawal symptoms. An exception to this is gender, for which there is substantial preclinical evidence to support causal associations between gonadal hormones and opioid effects (Huhn et al, 2018), and some limited human empirical evidence that gender may moderate withdrawal severity (Dunn et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…Manuscripts were included in this review if they (1) included a study abstract, (2) were published in English, (3) were a peer reviewed, original research article, (4) were published between the years of 1990 -March, 2018, (5) focused on outcome measures relevant to OUD treatment (e.g., continued drug use, comorbidities), (6) reported data that statistically compared outcomes as a function of sex, and (7) were conducted in human subjects. Manuscripts were excluded if (1) the primary outcome measures were pain, analgesia, and/or antinociception, or (2) only described results for one sex.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…Sex may be one of the most obvious potential biological predictors of disease, and there is growing recognition that men and women respond to drugs in a way that is qualitatively different and clinically meaningful. There is evidence from preclinical literature that sex hormones confer sex-based differences in opioid-based effects 6 , and animal studies suggest females are more vulnerable to the positive reinforcing effects of opioids that underlie acquisition of OUD and the negative reinforcing effects of opioids that promote dysregulation, escalation, and relapse that might also exacerbate the pace of OUD progression 7 . In the clinical literature, sex-based differences has been well characterized for stimulants, for which there is clear evidence that women's subjective experience to stimulants such as cocaine varies as a function of the menstrual cycle phase 8 .…”
Section: Introductionmentioning
confidence: 99%